2015
DOI: 10.1371/journal.pone.0136413
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Days of Heat Exposure on Firefighters’ Work Performance and Physiology

Abstract: This study assessed the accumulated effect of ambient heat on the performance of, and physiological and perceptual responses to, intermittent, simulated wildfire fighting tasks over three consecutive days. Firefighters (n = 36) were matched and allocated to either the CON (19°C) or HOT (33°C) condition. They performed three days of intermittent, self-paced simulated firefighting work, interspersed with physiological testing. Task repetitions were counted (and converted to distance or area) to determine work pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 43 publications
0
38
1
Order By: Relevance
“…Despite this limitation, there were no differences in daily fluid consumption between conditions and fluid intake was similar to levels demonstrated among firefighters completing multiple days of physical work in the heat, reported to be hydrated as determined using urine specific gravity (Larsen et al. ). Moreover, daily water intake exceeds recommended levels for adult males performing exercise in mild conditions (Gunga et al.…”
Section: Discussionmentioning
confidence: 63%
“…Despite this limitation, there were no differences in daily fluid consumption between conditions and fluid intake was similar to levels demonstrated among firefighters completing multiple days of physical work in the heat, reported to be hydrated as determined using urine specific gravity (Larsen et al. ). Moreover, daily water intake exceeds recommended levels for adult males performing exercise in mild conditions (Gunga et al.…”
Section: Discussionmentioning
confidence: 63%
“…Statistical significance was defined as p < 0.05 and post hoc pairwise comparisons were performed using a Bonferroni correction. The data analysed in the current study were secondary to the primary aims of the study, with primary outcomes published elsewhere [8,[12][13][14][15][48][49][50][51][52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Nutrients 2020, 12, 1160 4 of 18 previously published research findings can be found here [8,12,48]. The methodology and measures specific to the current study are presented below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations